Contemporary use of guideline‐based higher potency P2Y12 receptor inhibitor therapy in patients with moderate‐to‐high risk non‐ST‐segment elevation myocardial infarction: Results from the Canadian ACS reflective II cross‐sectional study. Issue 6 (13th May 2021) - Patel, Ashish; Goodman, Shaun G.; Tan, Mary; Suskin, Neville; McKelvie, Robert; Mathew, Andrew L.; Lutchmedial, Sohrab; Dehghani, Payam; Lavoie, Andrea J.; Huynh, Thao; Lavi, Shahar; Philipp, Roger; et al.
Abstract: Background: After myocardial infarction, guidelines recommend higher‐potency P2Y12 receptor inhibitors, namely ticagrelor and prasugrel, over clopidogrel. Hypothesis: We aimed to determine the contemporary use of higher‐potency antiplatelet therapy in Canadian patients with non‐ST‐elevation myocardial infarction (NSTEMI). Methods: A total of 684 moderate‐to‐high risk NSTEMI patients were enrolled in the prospective Canadian ACS Reflective II registry at 12 Canadian hospitals and three clinics in five provinces between July 2016 and May 2018. Multivariable logistic regression modeling was performed to assess factors independently associated with higher‐potency P2Y12 receptor inhibitor use at discharge. Results: At hospital discharge, 78.3% of patients were treated with a P2Y12 receptor inhibitor. Among patients discharged on a P2Y12 receptor inhibitor, use of higher‐potency P2Y12 receptor inhibitor was 61.4%. After adjustment, treatment in‐hospital with PCI (OR 4.48, 95%CI 3.34–6.03, p < .0001) was most strongly associated with higher use of higher‐potency P2Y12 receptor inhibitor, while oral anticoagulant use at discharge (OR 0.03, 95%CI 0.01–0.12, p < .0001), and atrial fibrillation (OR 0.40, 95%CI 0.17–0.98, p = .046) were most strongly associated with lower use of higher‐potency P2Y12 receptor inhibitor. Use of higher‐potency P2Y12 receptor inhibitor varied across provinces (range, 21.6%–78.9%). Discussion: In contemporary Canadian practice, approximately 60% of moderate‐to‐high risk NSTEMI patients discharged on a P2Y12 receptor inhibitor are treated with a higher‐potency P2Y12 receptor inhibitor. In addition to factors that increase risk of bleeding, interprovincial differences in practice patterns were associated with use of higher‐potency P2Y12 receptor inhibitor at discharge. Opportunities remain for further optimization of evidence‐based, guideline‐recommended antiplatelet therapy use.